Co-delivery of quercetin and caffeic-acid phenethyl ester by polymeric nanoparticles for improved antitumor efficacy in colon cancer cells - Colpan, Reyhan Dilsu; Erdemir, Aysegul (Journal of microencapsulation, 2021)
This study aimed to synthesise quercetin- caffeic-acid phenethyl ester (CAPE)-co-loaded poly(lactic-co-glycolic-acid) (PLGA) nanoparticles (QuCaNP) and investigate their anti-cancer activity on human colorectal carcinoma HT-29 cells. QuCaNPs were synthesised using single-emulsion (o/w) solvent evaporation method. Particle size, zeta potential, polydispersity index, in vitro release profile, and surface morphology of QuCaNPs were determined. Cytotoxicity, anti-migration, anti-proliferation and apoptotic activities of QuCaNPs were studied. Mean diameter of QuCaNP was 237.8 ± 9.670 nm, with a polydispersity index (PDI) of 0.340 ± 0.027. Encapsulation efficiency was 74.28% (quercetin) and 65.24% (CAPE). Particle size and drug content of QuCaNP remained stable for 30 days at −20 °C. The half-maximal inhibitory concentration (IC 50 ) values of QuCaNP-treated HT-29 cells were calculated as 11.2 µg/mL (24 h) and 8.2 µg/mL (48 h). QuCaNP treatment increased mRNA levels of caspase-3 (2.38 fold) and caspase-9 (2-fold) and expressions of key proteins in the intrinsic apoptosis pathway in HT-29 cells. Overall, our results demonstrated QuCaNPs exhibits improved anti-cancer activity on HT-29 cells.